Factors Relating To Ventilator-Associated Event - Yoszaria, Anang (Dewan Pimpinan Daerah Persatuan Perawat Nasional Indonesia Kota Blitar, 2024)
Mechanical ventilation is an oxygen therapy that is effective in saving the lives of critical patients in the intensive care unit (ICU). Prolonged use results in an increased risk of infection, in this case ventilator-associated pneumonia (VAP). In 2013, the United States Centers for Disease Control and Prevention redefined monitoring of the quality of care for patients using ventilators by moving away from the definition of ventilator-associated pneumonia ( VAP) to the definition of a ventilator-associated event (VAE) as a sustained increase in ventilator support after a period of stable or decreased ventilator support. For this reason, it is necessary to search for data regarding factors that influence ventilator-associated events. The literature search method was carried out based on articles published between 2019-2024 in accordance with the inclusion and exclusion criteria that had been determined using 1 database, namely Scopus. This literature search used PRISMA guidelines in carrying out the screening process. From the search results, 60 articles were obtained. After going through the screening process, there were 3 articles that met the criteria and will be analyzed. The results of the study from 3 pieces of literature show that the factors associated with ventilator-associated events are ventilator-associated events, namely the application of SDD (selective digestive decontamination, VILI (ventilator induced lung injury), lung atelectasis, excess fluid, including pulmonary edema, use of medication chlorhexidine mouthwash for oral care, spontaneous breath trials, early mobility, tracheostomy, use of vasopressors, transfusion overload, delirium, type of sedation (continuous or intermittent), type of sedation drug (midazolam, propofol), and analgesia drugs (fentanyl, morphine, remifentanil ), conditions related to infection, gender, age, presence of comorbidities, body mass index, and disease severity index. Reason for intubation. Intubation can be carried out in the ICU or elsewhere.